Large-scale 20K helium refrigeration system for the European Spallation Source. Issue 1 (1st May 2022) - Arnold, P; Zhang, J; Kolev, N; Ressel, M
Abstract: In 2016 Linde was awarded the contract to deliver the largest of its kind 20K helium refrigeration system to the European Spallation Source (ESS) in Lund, Sweden called Target Moderator Cryoplant (TMCP). A linear proton accelerator provides a high energetic pulsed beam to a rotating tungsten spallation target, generating fast neutrons. The TMCP helium cryogenic system will cool the liquid hydrogen circulating through the cryogenic moderator(s) which surround the spallation target. Thereby the neutrons are decelerated to form a useful radiation for the neutron instruments. The scope of delivery seems usual: cold box, two parallel compressors, oil removal and gas management systems and a jumper spool for performance testing. The requirements and the TMCP are unique: the refrigeration system is capable of a large range of cryogenic loads – guaranteed is from 4.9kW to above 30.3kW– with focus on maintaining efficiency over this range. The paper and presentation will cover the process design, the control strategies and the main results of the performance testing.